Efficacy and cost savings with the use of a minimal sedation / anxiolysis protocol for intra-articular corticosteroid injections in children with juvenile idiopathic arthritis: a retrospective review of prospectively collected data - Rotem Elitsur; April Hollenbeck; Laura Tasan; Kathryn S. Torok; Elaine Cassidy; Brian Blasiole; Erika Parsons; Chelsea Acock; Joseph Angelelli; Isabela-Cajiao Angelelli (BMC, 2019)
Abstract Background Intra-articular corticosteroid injections (IACI) are frequently used in the treatment of juvenile idiopathic arthritis. There is a paucity of evidence-based research describing methods of pain and anxiety control for this procedure. IACI were mostly performed under general anesthesia for children younger than 13 years old in our institution as of 2014. We started to integrate sedation services more commonly in our institution with the minimal sedation/anxiolysis (MSA) protocol outlined as an alternative to general anesthesia for IACI in 2015. The purpose of this study was to evaluate the effectiveness and cost savings of a minimal sedation protocol for intra-articular corticosteroid injections in juvenile idiopathic arthritis patients after instituting this protocol at our institution. Methods The MSA protocol included nitrous oxide, intranasal fentanyl, a topical numbing agent, acetaminophen, ibuprofen, ondansetron and child life intervention. A retrospective review of prospectively collected data was performed on a total of 80 consecutive patients with juvenile idiopathic arthritis who underwent joint injections using the protocol. Results The procedure was successfully completed in greater than 95% of the patients. The median pain score (measured on a verbal numeric scale of 0-10) reported by the patient was 1 (IQR 0-2.5), by the parent 1 (IQR 0-2), by the rheumatologist 1 (IQR 0-1), and by the sedationist 1 (IQR 0-1). Degree of motion during the procedure was reported by the rheumatologist and the sedationist as none in 68% of the patients, mild in 36% and moderate in 6%. Patient, parent, rheumatologist and sedationist rated satisfaction as very high in the vast majority (94%). Emesis was reported in only 2 (2.5%) patients, no significant adverse events were reported, and no patients progressed to a deeper level of sedation than intended. Financial analysis revealed a 33% cost reduction compared with the use of general anesthesia in the operating room. Conclusions A minimal sedation/anxiolysis protocol (including nitrous oxide, intranasal fentanyl, a topical numbing agent, acetaminophen, ibuprofen, ondansetron and child life intervention), provides safe and effective analgesia for intra-articular corticosteroid injection in a subset of patients with juvenile idiopathic arthritis and offers a lower cost alternative to general anesthesia.